Strategi Kepemimpinan Kepala Madrasah Dalam Membina Kompetensi Sosial Guru (Studi Kasus Di Madrasah Aliyah Swasta Pondok Pesantren Imam Muslim Kecamatan Sei Rampah Kabupaten Serdang Bedagai) - Az Zahra, Latifah; Sazali, Anwar; Syahlan, Ali (STAI Tebing Tinggi Deli, 2024)
This study aims to identify and analyze the leadership strategy of the madrasah head in improving the social competence of teachers at the Imam Muslim Private Aliyah Madrasah Islamic Boarding School Sei Rampah, Serdang Bedagai. This research uses a qualitative approach with case studies. This research uses two data sources, namely primary and secondary data with data collection techniques using interviews, observation and documentation. The results of this study include: The strategy of the Head of Madrasah Aliyah Swasta Pondok Pesantren Imam Muslim in improving the social competence of teachers: (1) Involving in education and training (2) Involving ustadz in MGMP activities (3) Conducting In House Training activities (4) Conducting supervision (5) Enforcing discipline (6) Motivating ustadz. Supporting and inhibiting factors in improving the social competence of ustadz: Supporting factors: (1) Good cooperation between the head of the madrasa and the ustadz. (2) Madrasah has human resources, all of which are S1 scholars. (3) The existence of motivation and encouragement to be better. (4) Good madrasah environment. (5) Many activities in support of improving the social competence of ustadz. Inhibiting factors: (1) Madrasah does not yet have facilities and infrastructure that support the social competence of ustadz to develop. (2) Madrasah has limited funds. (3) Different backgrounds of students.